2022
DOI: 10.3390/w14010122
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Economic Investment Evaluation of Wastewater Treatment Plant

Abstract: Improved Cost-Benefit Analysis (CBA) analysis requires a broader analytical framework, in order to perceive each project individually from the perspective of potentially measurable and significant effects on the environment and society as a whole. The main goal of our paper is to assess the financial and economic justification for variant V3 (as the most technically optimal) of the wastewater treatment plant (WWTP) construction project in Nov Dojran, North Macedonia, with the purpose of advancing municipal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The concept of sustainable wastewater management has been heavily articulated and should be considered through a multidisciplinary perspective (Ćetković et al 2022 ; Molinos-Senante et al 2010 ), highlighting the need for an economic analysis, as suggested by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of sustainable wastewater management has been heavily articulated and should be considered through a multidisciplinary perspective (Ćetković et al 2022 ; Molinos-Senante et al 2010 ), highlighting the need for an economic analysis, as suggested by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental benefits are calculated using the shadow price approach developed "to assess internal (which is easy to monetize) but also external economic impacts" (Ćetković et al, 2022;Molinos-Senante et al, 2011 and. The shadow price is the monetary value assigned to an abstract or intangible commodity which, not traded in the market, must be included in an economic evaluation (Sartori et al, 2014).…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…The technical solutions for those projects are available and well developed, but they come with a huge financial demand since they are very expensive to implement (Fernandez et al, 2009). In general terms, the costs of the investments are well known but not so much the benefits, particularly in the case of environmental benefits where different approaches prevail (Chen and Wang, 2009;Godfrey et al, 2009;Hernández et al, 2006;Molinos-Senante et al, 2010;Ćetković et al, 2022). Previous research focus on water reuse for environmental purposes (Birol et al, 2010;Chen et Wang, 2009;Kihila et al, 2014;Molinos-Senante et al, 2010;Verlicchi et al, 2012) while economic and financial feasibility evaluations are often missing especially when the reuse in irrigation is the main option.…”
Section: Introductionmentioning
confidence: 99%
“…The technical solutions for those projects are available and well developed, but they come with a huge financial demand since they are very expensive to implement (Fernandez et al, 2009). In general terms, the costs of the investments are well known but not so much the benefits, particularly in the case of environmental benefits where different approaches prevail (Chen and Wang, 2009;Godfrey et al, 2009;Hernández et al, 2006;Molinos-Senante et al, 2010;Ćetković et al, 2022). Previous research focus on water reuse for environmental purposes (Birol et al, 2010;Chen et Wang, 2009;Kihila et al, 2014;Molinos-Senante et al, 2010;Verlicchi et al, 2012) while economic and financial feasibility evaluations are often missing especially when the reuse in irrigation is the main option.…”
Section: Introductionmentioning
confidence: 99%